2021
DOI: 10.1186/s13578-021-00564-x
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolic acid and anacardic acid are specific covalent inhibitors of SARS-CoV-2 cysteine proteases

Abstract: Background In the urgent campaign to develop therapeutics against SARS-CoV-2, natural products have been an important source of new lead compounds. Results We herein identified two natural products, ginkgolic acid and anacardic acid, as inhibitors using a high-throughput screen targeting the SARS-CoV-2 papain-like protease (PLpro). Moreover, our study demonstrated that the two hit compounds are dual inhibitors targeting the SARS-CoV-2 3-chymotrypsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 17 publications
1
48
1
1
Order By: Relevance
“…Cellular screenings have not been performed for these molecules and there is a general lack of knowledge concerning their efficacy and safety in a relevant biological environment, though ebselen is largely considered non-cytotoxic. On the other hand, drug repurposing in silico protocols have highlighted some natural and synthetic products as dual M pro and PL pro inhibitors [ 52 , 53 ]. Ginkgolic and anacardic acids, in particular, showed moderate potencies in enzymatic assays, especially over PL pro , cellular plaque formation IC 50 s in the high micromolar range, but also comparable CC 50 values [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular screenings have not been performed for these molecules and there is a general lack of knowledge concerning their efficacy and safety in a relevant biological environment, though ebselen is largely considered non-cytotoxic. On the other hand, drug repurposing in silico protocols have highlighted some natural and synthetic products as dual M pro and PL pro inhibitors [ 52 , 53 ]. Ginkgolic and anacardic acids, in particular, showed moderate potencies in enzymatic assays, especially over PL pro , cellular plaque formation IC 50 s in the high micromolar range, but also comparable CC 50 values [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, drug repurposing in silico protocols have highlighted some natural and synthetic products as dual M pro and PL pro inhibitors [ 52 , 53 ]. Ginkgolic and anacardic acids, in particular, showed moderate potencies in enzymatic assays, especially over PL pro , cellular plaque formation IC 50 s in the high micromolar range, but also comparable CC 50 values [ 52 ]. Ma and coworkers also showed that several compounds identified through in silico screening as potential multitarget proteases inhibitors completely lack of cellular antiviral activity, despite the high potencies showed in enzymatic assays.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we provide a set of previously published redocked compounds with reported half maximal inhibitory concentration (IC 50 ) values against 3CL pro [ 38 , 73 , 87 , 88 ] and PL pro [ 40 , [89] , [90] , [91] , [92] ] to give the interested reader more detailed view on the docking score vs. dose concentration relation of in vitro tested compounds. Refer to the supplementary materials in respective .xlsx documents, sheets IC 50 _dockings.…”
Section: Discussionmentioning
confidence: 99%
“…The most potent inhibitor was papyriflavonol A (82), which presented anti-SARS-CoV PL pro activity with an IC 50 of 3.70 μM (Park et al, 2017). In addition to these excellent studies of this team, Chen et al recently reported ginkgolic acid (90) and anacardic acid (91) as potent covalent inhibitors of both PL pro and 3CL pro of SARS-CoV-2, and the two compounds showed inhibitory activities against SARS-CoV-2 replication in vitro at non-toxic concentrations (Chen et al, 2021). Some other studies only reported on natural bioactive molecules that inhibited PL pro (Figure 3C).…”
Section: Viral Proteasesmentioning
confidence: 85%